The relationship between job characteristics towards job satisfaction: a case study at Kuala Lumpur Airport Services Sdn. Bhd. / Nuraszalina Booty Asmara Booty - Asmara Booty, Nuraszalina Booty (Faculty of Business and Management, 2009)
The most important element in an organization is about job satisfaction among workers. We can said that job satisfaction is the starting point in order to make sure the organization really success in their business. But, this key point always been unrealized by the organization because busy thinking on how to create more money and benefit day by day. The organization may achieve their target in business, but they will face a lot of problems if their workers feel unsatisfied with their job. As a result, the employees will create problems on employees’ productivity, absenteeism, turnover rates, as well as disciplinary problem. Kuala Lumpur Airport Services Sdn. Bhd. (KLAS) has about 1,400 employees and also faced the common problems. Even though KLAS have been provided all their employees with excellent benefits, some of the employees still feel unsatisfied with their job. Due to the important factor to the organization, that is why me as the researcher decided to know deeper and do research on the relationship between job characteristics (salary, reward, job stress, employee attitudes, teamwork) towards the level of job satisfaction. In this study of research, job characteristics act as independent variables, while job satisfaction act as dependent variable. The scope of study involves 50 of respondents and chooses non-probability as sampling technique. The questionnaire is divided into several sections. Furthermore, this studies using primary and secondary data. Findings are interpreted using several methods of analysis. As conclusion, there is a relationship between reward and Job Satisfaction. The recommendations that been recommended is to reconstruct the compensation packages, developing a service point, and, arrange the duty roaster not too tight.